ROLE OF IONIC LIQUIDS FOR EFFECTIVE THERMODYNAMIC METHANE HYDRATE INHIBITION - ISHTIAQ, UMAIR (2018)
In petroleum exploration, production and transportation operations, methane hydrates are considered nuisance and problematic as they pose acute flow assurance disruptions, economic concerns and safety hazards.